CDK9 binds and activates SGK3 to promote cardiac repair after injury via the GSK-3β/β-catenin pathway - Sun, Jiateng; Yang, Tongtong; Wei, Tianwen; Zhou, Liuhua; Shan, Tiankai; Chen, Jiawen; Gu, Lingfeng; Chen, Bingrui; Liu, Liu; Jiang, Qiqi; Du, Chong; Ma, Yao; et al. (Frontiers in Cardiovascular Medicine, 2022)
The mammalian heart possesses entire regeneration capacity after birth, which is lost in adulthood. The role of the kinase network in myocardial regeneration remains largely elusive. SGK3 (threonine-protein kinase 3) is a functional kinase we identified previously with the capacity to promote cardiomyocyte proliferation and cardiac repair after myocardial infarction. However, the upstream signals regulating SGK3 are still unknown. Based on the quantitative phosphoproteomics data and pulldown assay, we identified cyclin-dependent kinase 9 (CDK9) as a novel therapeutic target in regeneration therapy. The direct combination between CDK9 and SGK3 was further confirmed by co-immunoprecipitation (Co-IP). CDK9 is highly expressed in the newborn period and rarely detected in the adult myocardium. In vitro, the proliferation ratio of primary cardiomyocytes was significantly elevated by CDK9 overexpression while inhibited by CDK9 knockdown. In vivo, inhibition of CDK9 shortened the time window of cardiac regeneration after apical resection (AR) in neonatal mice, while overexpression of CDK9 significantly promoted mature cardiomyocytes (CMs) to re-enter the cell cycle and cardiac repair after myocardial infarction (MI) in adult mice. Mechanistically, CDK9 promoted cardiac repair by directly activating SGK3 and downstream GSK-3β/β-catenin pathway. Consequently, our study indicated that CDK9 might be a novel target for MI therapy by stimulating myocardial regeneration.